Comparative insight into the genomic landscape of SARS‐CoV‐2 and identification of mutations associated with the origin of infection and diversity. Issue 4 (29th December 2020) - Mishra, Divya; Suri, Gurparsad Singh; Kaur, Gurleen; Tiwari, Manish
Abstract: The analyses of 2325 severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) genomes revealed 107, 162, and 65 nucleotide substitutions in the coding region of SARS‐CoV‐2 from the three continents America, Europe, and Asia, respectively. Of these nucleotide substitutions 58, 94, and 37 were nonsynonymous types mostly present in the Nsp2, Nsp3, Spike, and ORF9. A continent‐specific phylogram analyses clustered the SARS‐CoV‐2 in the different group based on the frequency of nucleotide substitutions. Detailed analyses about the continent‐specific amino acid changes and their effectiveness by SNAP2 software was investigated. We found 11 common nonsynonymous mutations; among them, two novel effective mutations were identified in ORF9 (S194L and S202N). Intriguingly, ORF9 encodes nucleocapsid phosphoprotein possessing many effective mutations across continents and could be a potential candidate after the spike protein for studying the role of mutation in viral assembly and pathogenesis. Among the two forms of certain frequent mutation, one form is more prevalent in Europe continents (Nsp12:L314, Nsp13:P504, Nsp13:Y541, Spike:G614, and ORF8:L84) while other forms are more prevalent in American (Nsp12:P314, Nsp13:L504, Nsp13:C541, Spike:D614, and ORF8:L84) and Asian continents (Spike:D614), indicating the spatial and temporal dynamics of SARS‐CoV‐2. We identified highly conserved 38 regions and among these regions, 11 siRNAs were predicted on stringent criteria that can be used to suppress the expression of viral genes and the corresponding reduction of human viral infections. The present investigation provides information on different mutations and will pave the way for differentiating strains based on virulence and their use in the development of better antiviral therapy. Highlights: This study provides different types of mutations occurring in SARS‐CoV‐2 genomes across continents. The mutations hold an explanation for the varied pathogenicity and resistance to antiviral therapies. The nonsynonymous mutations leading to amino acid changes also explain the travel of infection from its place of the outbreak to the world and the evolution of virus upon interaction with different geography and demography.